Phanerozoic geological evolution of Northern and Central Africa: An overview. - (:unkn) unknown (My University, 2005)
The principal paleogeographic characteristics of North and Central Africa during the Paleozoic were the permanency of large exposed lands over central Africa, surrounded by northerly and northwesterly dipping pediplanes episodically flooded by epicontinental seas related to the Paleotethys Ocean. The intra-continental Congo–Zaire Basin was also a long-lived feature, as well as the Somali Basin from Late Carboniferous times, in conjunction with the development of the Karoo basins of southern Africa. This configuration, in combination with eustatic sea-level fluctuations, had a strong influence on facies distributions. Significant transgressions occurred during the Early Cambrian, Tremadocian, Llandovery, Middle to Late Devonian, Early Carboniferous, and Moscovian. The Paleozoic tectonic history shows an alternation of long periods of predominantly gentle basin subsidence and short periods of gentle folding and occasionally basin inversion. Some local rift basins developed episodically, located mainly along the northern African– Arabian plate margin and near the West African Craton/Pan-African Belt suture. Several arches or spurs, mainly N–S to NE– SW trending and inherited from late Pan-African fault swarms, played an important role. The Nubia Province was the site of numerous alkaline anorogenic intrusions, starting in Ordovician times, and subsequently formed a large swell. Paleozoic compressional events occurred in the latest Early Cambrian (‘‘Iskelian''), Medial Ordovician to earliest Silurian (‘‘pre-Caradoc'' and ‘‘Taconian''), the end Silurian (‘‘Early Acadian'' or ‘‘Ardennian''), mid-Devonian (‘‘Mid-Acadian''), the end Devonian (‘‘Late Acadian'' or ‘‘Bretonnian''), the earliest Serpukhovian (‘‘Sudetic''), and the latest Carboniferous–earliest Permian (‘‘Alleghanian'' or ‘‘Asturian''). The strongest deformations, including folding, thrusting, and active strike-slip faulting, were registered in
Keywords: African Research